The Organ as a Mirror of its Time. North European reflections, 1610-2000 - Snyder, Kerala J. (Oxford Oxford university press, 2002)
Because it has always represented a rich collaboration of the music, art, architecture, handicraft and science of its day, the organ, more than any other instrument, continues to reflect the spirit of the age in which it was built. The Organ as a Mirror of its Time, the first book to consider this instrument's historical and cultural significance, reflects the efforts of twenty leading scholars of the organ.The book chronicles the history of six organs in Scandinavia and Northern Germany, at least one specimen for every century from 1600 to the present. By considering their original contexts and their histories since they were built, as well as the extraordinary coincidences that link them together, the book offers a unique perspective on the cultural history of northern Europe. A CD with appropriate repertoire played on each of the six instruments accompanies the book.
Keywords: Organ; Cuckoo